Sustainable Flood Disaster Risk Mitigation in Wonoasri Village, Tempurejo District, Jember Regency - Krisnamurti Krisnamurti; Rendy Setiawan; Luh Putu Indah Budyawati; Anik Suwandari; Ika Barokah Suryaningsih; Galih Wicaksono; Ifa Annisa Sabrina; Karimatul Faiziyyah (Jurnal Pengabdian Masyarakat IPTEKS, 2026)
Wonoasri Village is one of the villages located in Tempurejo District, Jember Regency. This village is a buffer village for Meru Betiri National Park with regional characteristics of lowlands, hills, and forests flanked by 2 large rivers, namely the Mayang River and the Curahnongko River. Based on observations by the PKM team, this village is prone to flooding due to high rainfall, climate change, and poor natural resource management. Therefore, the PKM team aims to carry out disaster mitigation, especially mitigating the risk of flooding impacts in a sustainable manner. The community service implementation method uses 5 stages: funding for rubber boat grants, funding for supporting equipment, training and practice, mentoring and activity evaluation. The results obtained are that there are 4 main problems that cause flooding in this village: high and prolonged rainfall, sloping topography of the area, deforestation in the upper reaches of the river, and poor drainage systems. The PKM team has handed over a grant of rubber boats and other equipment that is useful for flood mitigation efforts accompanied by counseling, training and direct surveys at flood-affected locations. The activity was successful, as seen from the increase in the level of insight and skills of community members, village governments, and the Destanas in efforts to mitigate the impact of flood disaster risks.